Design And Fabrication Of A Prototype Model Of Vibration Isolation Table - Abdul Muthalif, Asan Gani (s.n, 2012)
Excessive vibration affects performance of many electrical and electronics equipment. One of such equipment is laser beam transmitter for data transmission via free space optics (FSO). Achieving the desired performances of the equipment will require a vibration isolation table to isolate the equipment's from the surrounding vibrations.